2020
DOI: 10.1007/s10792-020-01549-4
|View full text |Cite
|
Sign up to set email alerts
|

Is optical coherence tomography angiography a useful tool in the screening of hydroxychloroquine retinopathy?

Abstract: Purpose To detect the early changes in retinal vasculature via optical coherence tomography angiography (OCTA) by comparing the quantitative OCTA parameters in the group of patients who were using hydroxychloroquine (HCQ) or not. Methods This was a cross-sectional, comparative, and observational study. The patients who were newly or previously prescribed HCQ for an autoimmune disease were included. OCTA imaging was performed via OCT RT XR Avanti with AngioVue software (Optivue Inc, Freemont, CA). The study gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…To the best of our knowledge, limited studies have been conducted on the use of OCTA in the evaluation of HCQ-induced retinopathy, the results of which are also controversial. Some studies have evaluated OCTA changes between healthy individuals and patients with a history of HCQ use, and some studies have evaluated OCTA changes between High Risk (HCQ users over 5 years) and Low Risk (HCQ users less than 5 years) [ 22 , 23 , 28 , 30 32 ]. A review of studies in this field shows confusing results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, limited studies have been conducted on the use of OCTA in the evaluation of HCQ-induced retinopathy, the results of which are also controversial. Some studies have evaluated OCTA changes between healthy individuals and patients with a history of HCQ use, and some studies have evaluated OCTA changes between High Risk (HCQ users over 5 years) and Low Risk (HCQ users less than 5 years) [ 22 , 23 , 28 , 30 32 ]. A review of studies in this field shows confusing results.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Tarakcioglu et al, which was performed among 102 patients, No significant difference was observed between the HCQ treatment group and the control group in the parameters of FAZ, Flow Area, vascular density, SCP and DCP [ 28 ]. Based on our results, the patients in both groups were similar in the parameters of FAZ, Flow Area and SCP vascular density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have evaluated OCTA changes between healthy individuals and patients with a history of HCQ use, and some studies have evaluated OCTA changes between High Risk (HCQ users over 5 years) and Low Risk (HCQ users less than 5 years). (22,23,28,(30)(31)(32) A review of studies in this eld shows confusing results. To our knowledge, no study has been performed to evaluate changes in OCTA among patients with HCQ-induced retinopathy based on mfERG and those without retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Images with signal strength index (SSI) less than 40 or had an artifact were not analyzed. (28)Finally, based on mfERG criteria, we divided patients into normal mfERG and abnormal mfERG groups. We also divided patients into separate SLE and RA subgroups.…”
Section: Methodsmentioning
confidence: 99%